Mind mapping w nauczaniu i uczeniu się języka obcego - Łyp-Bielecka, Aleksandra (Neofilolog, 2019)
Mind mapping, developed 1972 by Tony Buzan, is a graphic way of representing ideas and concepts. The article shows the possibilities and benefits of using mind mapping in foreign language learning and teaching. Additionally, the article describes some of the computer applications which can be used to draw a mind map.